Storage stability and morphology of latex modified bitumen - Usman, A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Bitumen modification is done to enhance the properties of bitumen related to elasticity, temperature susceptibility, softening point etc. This research intends to assess the effects of natural rubber latex (NRL) in liquid form as a bitumen modifier. Conventional tests, temperature susceptibility and phase separation due to hot storage were investigated using two separate mixing speeds of 1200 and 1300 revolution per minutes (rev/min). Morphology due to the addition of NRL has also been explored utilizing Atomic Force Microscopy (AFM). NRL was incorporated into the bitumen by weight of the binder for the modification at three different amounts (i.e. 3, 5 and 6). Based on the softening point, penetration value, temperature susceptibility and storage stability the latex-modified asphalt binder were analyzed. Results of the investigation showed that owing to enhancement in viscoelastic properties, the latex-modified asphalt binder will not undergo phase separation during hot temperature storage. Meanwhile, a uniform dispersed network was indicated by the morphological analysis with the presence of three phases of para, peri and cata. It can be deduced from the results obtained that the latex-modified asphalt binders will perform better in terms of softening point, penetration value and susceptibility due to temperature. Â© BEIESP.